(untitled) (Bodhi Path, 2024)
The significance of the threefold Buddha Vaishakh Purnima in Pali Tripitaka literature is a legacy for the entire global community. This day reflects three important events related to the life of Lord Buddha. In which the birth of Siddhartha Gautama, the attainment of Buddhahood, and the Mahaparinirvana are prominent. All these three events and the teachings of Lord Buddha’s Dhamma (teachings) such as- Sheel, Samadhi, Prajna, etc., which are the path to liberation from the sufferings of the entire human race from physical life to worldly life. By adopting which the seeker can make his life valuable and achieve his goal (Nirvana). The basis of this research paper is Pali Tripitaka literature (original) and Vipassana Visodhana Vinyasa, Igatpuri, Nashik’s Pali and Anupitaka literature as secondary sources.